Funkcjonowanie uniwersytetu w środowisku Zielonej Góry = University performance in the area of Zielona Góra - Wołk, Zdzisław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The University of Zielona Gora is one of the youngest in the country but in the life of our city it plays a very important role with its academic and cultural potential. Its academic development is performed generally through its own efforts, which is a difficult task for a young university situated in the province of a country.
Keywords: Zielona Góra; Uniwersytet Zielonogórski; środowisko lokalne